Association between multi nodular goitre and thyroid malignancy at a tertiary care centre - M., Sreenidhi G.; S., Jyothi (International Surgery Journal, 2021)
Background: Over the past few decades, the incidence of thyroid cancer has dramatically increased. Thyroid malignancy in multinodular goitre is considered to be high and these occult malignancies are detected only in post operative histopathological analysis. The study helps in finding association between multinodular goitre and thyroid malignancy. Objective was to find the association between multinodular goitre and thyroid malignancy in those who underwent total thyroidectomy. Methods: A cross sectional study conducted in department of general surgery, KIMS hospital, Bangalore. The 236 randomized cases of multinodular goitre who underwent total thyroidectomy were selected. Patients underwent thorough clinical examination pre operatively and were reassessed in post-operative period following surgery. Later, histopathology report on thyroidectomy specimen of the patients were obtained. This report was considered the gold standard for the diagnosis of thyroid malignancy. Results: Occult malignancies were commoner in middle aged females. Most of the patients in the study underwent total thyroidectomy. The prevalence of thyroid malignancy in our study was found to be 7.2%. In the study, 17 incidental malignancies were papillary carcinomas. It revealed a highly significant relation between the lymphocytic thyroiditis and occult malignancy (p<0.0001) Conclusions: The prevalence of malignancy in multinodular goitre is 7.2%. The only variant of incidental malignancy detected in histopathological examination of excised thyroid was papillary carcinoma. There is a statistically significant association between presence of thyroiditis in preoperative FNA and presence of occult malignancy carcinoma.